Dialectics of Lexical and Cultural Semantics: A Linguistic and Anthropological Perspective - Neldi Harianto; Rengki Afria; Julisah Izar; Denny Defrianti (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025)
This study explores the dialectics between lexical semantics and cultural semantics through linguistic and anthropological perspectives, aiming to reveal the dynamic interplay between language meaning and cultural contexts. Lexical semantics analyzes the structural relations of word meaning within the language system, while cultural semantics emphasizes the role of social values, norms, and collective experiences in shaping meaning. Using a qualitative methodology that combines discourse analysis and linguistic ethnography, the findings highlight a reciprocal relationship: lexical meaning is enriched by cultural dimensions, and cultural concepts are mediated through lexical expressions. The study underscores the necessity of integrating both approaches to achieve a more comprehensive understanding of language and its socio-cultural realities. The results contribute to advancing interdisciplinary semantic studies and fostering cross-cultural communication.